ZAKAT PRODUKTIF SEBAGAI INSTRUMEN PEMBANGUNAN EKONOMI DAERAH: Productive Zakat As An Instrument Of Regional Economic Development - effendi, orien; Alfauzi, Ro'is; Sukma, Habibullah (ISTIDLAL, 2025)
Zakat is a basic principle brought by Islamic teachings, which are oriented towards the benefit of the ummah. Regarding the procedures for managing zakat, it is expected that it is an effort to encourage prosperity, economic development, and a strategy to achieve the goals aspired by a nation and a country. So that the poverty and unemployment rates, as well as the gap in the social class of society, will be resolved and the creation of a prosperous, just and prosperous society by the goals of the nation and country. However, in the field, it shows that the current implementation and management of zakat is less effective and still uses classic methods, innovation, and professional work are expected to be far from the desired expectations. So naturally, there are still very poor people in various places and all over the region. This research uses qualitative methods to explain the intent and purpose of writing. And this writing also offers zakat as an economic instrument for regional development, which is based on humanity and strong tolerance between religious communities. Thus there is nothing but effective zakat management and management so that welfare and economic prosperity are expected to be created. As is well known, good zakat management is a requirement and condition for the creation of a clear, accountable, and transparent economy, to avoid corrupt behavior. The management of zakat management uses the principles and rules of sharia law based on tolerance so that the goal is by the principles of the Pancasila Ideology